Implementation Of Development Of Integrity Zones Towards Wbk (Corruption-Free Area) And Wbbm (Clean Service Bureaucracy Area) In Implementation Of Government To Fulfill The Community's Rights To - Sudictar, Rizkian Fajar; Hayati, Tri (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2022)
The Government of Indonesia's efforts to reform the bureaucracy is not something new. For the public to feel the results of the acceleration of Bureaucratic Reform that has been carried out by the government, especially in work units, the Ministry of Empowerment of State Apparatus and Bureaucratic Reform (Ministry of PAN RB) has issued Ministerial Regulation of PAN RB No. 52 of 2014 concerning Guidelines for the Development of an Integrity Zone towards a Corruption-Free Area and a Clean Bureaucratic Area Serving in Government Agencies, which was later refined by Ministerial Regulation of PAN RB No. 10 of 2019. In the context of the right to public services as a constitutional right of every citizen, can the development of this integrity zone be able to solve the problem of the poor quality of public services by the government? The research method used is a qualitative research method with a statutory approach and then analyzes the implementation in the field. The results of the study indicate that the current Integrity Zone implementation has not been maximized in fulfilling the constitutional rights of citizens related to public services and the fulfillment of economic, social, cultural rights (ekosob) as implications for public services. This is due to several reasons that the Integrity Zone evaluation notes. Therefore, the formulation of a strategy to accelerate the Integrity Zone needs to be carried out as a solution for providing appropriate public services.